The comparison of carbohydrate, fiber, and immunoglobulin-A levels in feces against stunting children in Tuban Regency - Rivan Virlando Suryadinata; Heru Wijono; Firstylo Valiant Putra Sanwersko; Yosafat Elohimio Susanto; Amelia Lorensia (PAGEPress Publications, 2024)
Stunting in children under five years old is a major health problem in Indonesia. A compromised immune system in stunted children increases the risk of infection which has an impact on morbidity and mortality. Moreover, food intake is one of the causes of decreased immunity, where carbohydrate, fiber, and immunoglobulin-A levels in the intestine are related to the immunity of children under five years old. The assessment of feces content can provide an overview of carbohydrates, fiber, and immunoglobulin-A levels in the intestine. Therefore, this study aimed to determine the comparison of carbohydrate, fiber, and immunoglobulin-A levels in feces for stunted children. An observational method with a case-control design was used, and it was conducted in Tuban Regency from May to July 2023. Forty stool samples were obtained from 20 stunted children and 20 non-stunted children who were tested for carbohydrates, fiber, and immunoglobulin-A. Subsequently, the data were analyzed with a comparison test to determine the differences between the two groups. The results showed that carbohydrate and immunoglobulin-A levels were higher, while fiber levels in feces were lower in stunted children (p≥0.05). It was concluded that there were differences in levels of carbohydrates, fiber, and immunoglobulin-A in the intestines of stunted children.